Rupture of pacemaker electrode insulator due to subclavian entrapment. Case report - Meza Aquino, Miguel Alfonso (2022)
We present the case of an 82-year-old male patient with a history of single-chamber pacemaker implantation 7 years ago, due to third-degree atrioventricular block, who experienced presyncope. Telemetry showed a warning of possible electrode lead damage and ventricular noise input coinciding with capture failure, so the entire pacing system was programmed to be replaced. During the intervention, breakage of the electrode insulator was observed. The subclavian approach can cause damage to the electrode due to entrapment in the soft tissues it passes through before entering the venous system and iterative stretching. Insulator breakage may manifest as loss of capture and presence of noise on the electrocardiogram, drop in lead impedance, and suggestive radiographic images. The axillary approach is a safe and effective option and is therefore recommended for transvenous lead implantation.